A Real-Time Multiaperture Omnidirectional Visual Sensor Based on an Interconnected Network of Smart Cameras - Seyid, Kerem; Popovic, Vladan; Cogal, Omer; Akin, Abdulkadir; Afshari, Hossein; Schmid, Alexandre; Leblebici, Yusuf (IEEE transactions on circuits and systems for video technology, 2015)
Centralized and multilevel implementations of the Panoptic omnidirectional multiaperture visual system were previously presented by us, relying on the transmission of all camera outputs to a single central processing node for omnidirectional image and video reconstruction. In this paper, a novel distributed and parallel implementation of the omnidirectional vision reconstruction algorithm of the Panoptic system is presented. The parallel approach aims to overcome the scalability problems and memory bandwidth limitations of the centralized approach. The real-time hardware implementation is presented for camera modules with image processing, memory, and interconnectivity features. A methodology is introduced for the arrangement of camera modules with interconnectivity feature into a target interconnection network topology. A unique custom-made multiple-field-programmable gate array hardware platform is introduced for the implementation of an interconnected network of 49 camera prototype Panoptic system. A hardware architecture based on presented hardware platform enabling the real-time implementation of the blending algorithms is presented, along with the imaging results and resource utilization. The real-time implementation results of the implemented omnivision application on the mentioned prototype are demonstrated.